2004
DOI: 10.1159/000075962
|View full text |Cite
|
Sign up to set email alerts
|

Survival Rates after Radical Cystectomy according to Tumor Stage of Bladder Carcinoma at First Presentation

Abstract: Introduction: The aim of this study was to establish to what extent the survival rates of muscle-invasive bladder carcinoma are influenced by the tumor stage at initial presentation. Patients and Methods: This study examined the clinical course of 230 patients who underwent radical cystectomy for bladder carcinoma from 1992 to 2002. The patients were divided into three groups according to the histological results of the initial and final transurethral tumor resection (TURB). In group 1 (n = 41) radical cystect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
46
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 28 publications
8
46
0
2
Order By: Relevance
“…No other factor biasing CSS was noted in the present series. The ratio of patients with secondary MIBC of all patients undergoing RC for MIBC in the present series was 25% and thus within the range of previous series (21.4 to 29.4%) [18,19,20,21,22]. No differences in e.g.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…No other factor biasing CSS was noted in the present series. The ratio of patients with secondary MIBC of all patients undergoing RC for MIBC in the present series was 25% and thus within the range of previous series (21.4 to 29.4%) [18,19,20,21,22]. No differences in e.g.…”
Section: Discussionsupporting
confidence: 84%
“…'s series was larger than the present one, it was assessed in retrospect from various institutions while the present series was assessed prospectively with homogeneous treatment pattern due to institutional guidelines of one centre. In analogy to the present analyses, those series found no differences in outcome between primary versus secondary MIBC [17,18]. A more recent retrospective series by de Vries et al [19] assessing 134 and 54 patients with primary and secondary MIBC, respectively, found comparable survival rates.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…For organ confined lymph node negative T2 tumors, May et al, reported a 74% progression free 5 year survival rate, which was very close to the ratios given for T1 tumors (18). In a study by Wishnow and colleagues, 5 year mean survival and disease free survival rates after radical cystectomy, were 82 and 77%, respectively for patients with Stage B disease (19).…”
Section: Commentsmentioning
confidence: 62%
“…Considering this, RT would play a role in the treatment of tumors invading deeper layers and in eventually involved lymph nodes. The results presented in Weiss's study (12) seem to be superior when compared to TURB studies followed by intravesical BCG (40,41) and are relatively equivalent to radical cystectomy (42). This suggests that TURB followed by radiochemotherapy may be an adequate treatment for patients with high risk T1 stage.…”
Section: Multimodal Therapymentioning
confidence: 95%